Numerical study of jet-flap interaction noise and a procedure for designing thrust gates - Yupa Villanueva, Renatto Marcello (2021)
Descargue el texto completo en el repositorio institucional de la Universidade Federal de Santa Catarina: https://repositorio.ufsc.br/handle/123456789/221310